The reality of extra-curricular theatrical activities in the Algerian school from the point of view of theater supervisors in the intermediate stage (a field study of some mediums in the city of M'sila) - Guenfoud, Hadda; BELHOCINE RAHOUI , Abassia (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2022)
The study aimed to identify the reality of extra-curricular theatrical activities in the Algerian school from the point of view of the theater supervisors in the intermediate stage. The average? The main hypothesis was as follows: There are extra-curricular theatrical activities in the Algerian school from the point of view of the supervisors of the intermediate stage. To carry out this study, the most appropriate descriptive analytical approach was used for this type of studies, and the research community represented the supervisors of the school theater for some averages. The city of M'sila was chosen, and my purpose is a simple random sample formed by (04) a theater supervisor, based on the interview form tool for the sample members. The school’s goals include theatrical activities, and there are positive aspects to extra-curricular theatrical activities because it develops the students’ abilities and consolidates all educational, moral and aesthetic values. Mechanical and health, and it enhances talents and artistic and emotional creativity in the Algerian school from the point of view of the stage supervisors at the intermediate stage. As stated in the study’s recommendations, it is necessary to cooperate with teachers and to avoid misunderstanding of extracurricular theatrical activities as a recreational work and waste of time, and to conduct more studies on the importance of extracurricular theatrical activities and the elements of their employment and obstacles to their use.